Hepatic mitochondrial dysfunction in Friedreich Ataxia - Stüwe Sven H; Goetze Oliver; Arning Larissa; Banasch Matthias; Schmidt Wolfgang E; Schöls Ludger; Saft Carsten (BMC Neurology, 2011)
Abstract Background Mitochondrial dysfunction due to respiratory chain impairment is a key feature in pathogenesis of Friedreich ataxia. Friedreich ataxia affects the nervous system, heart and pancreas. Methods We assessed hepatic mitochondrial function by 13C-methionine-breath-test in 16 Friedreich ataxia patients and matched healthy controls. Results Patients exhaled significantly smaller amounts of 13CO2 over 90 minutes. Maximal exhaled percentage dose of 13CO2 recovery was reduced compared to controls. Conclusions 13C-methionine-breath-test indicates subclinical hepatic mitochondrial dysfunction in Friedreich ataxia but did not correlate with GAA repeat lengths, disease duration or disease severity.